2006
DOI: 10.1080/13547500600572764
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methodological and biological influences on the collection and composition of exhaled breath condensate

Abstract: The purpose of this inter-species comparison (calves and pigs) was to identify methodological and biological influences on the collection and composition of exhaled breath condensate (EBC). A total of 352 EBC samples were collected, whilst variables of ventilation were registered in parallel. Partial pressure of carbon dioxide (pCO2) and pH were analysed in non-degassed EBC samples. The concentration of total protein in EBC was measured colorimetrically. In both species, lung function was evaluated before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 54 publications
(91 reference statements)
4
38
0
Order By: Relevance
“…The mean pH of neat EBC was slightly higher than previous reports in horses with and without LAI , calves and pigs . The mean pH of deaerated EBC was comparable to previous reports in healthy horses, human subjects and dogs .…”
Section: Discussionsupporting
confidence: 69%
“…The mean pH of neat EBC was slightly higher than previous reports in horses with and without LAI , calves and pigs . The mean pH of deaerated EBC was comparable to previous reports in healthy horses, human subjects and dogs .…”
Section: Discussionsupporting
confidence: 69%
“…An EBC sampling system (ECoScreen, Viasys Healthcare) was connected to the facemask as previously described [30]. The animal was allowed to inhale only filtered ambient air (PALL breathing system filter, Pall Europe Ltd, Portsmouth, UK) in order to avoid contamination of EBC by inhaled ambient particles.…”
Section: Collection Of Exhaled Breath Condensate Samplesmentioning
confidence: 99%
“…Despite so, findings in animal models have identified that pCO 2 in EBC is negatively dependent on duration of collection [ 44 ]. A standardised collection time is therefore necessary in future EBC studies.…”
Section: Duration and Efficiency Of Ebc Collection Devicesmentioning
confidence: 99%